The genus Hourangia in China and a description of Aureoboletus erythraeus sp. nov. - Wang, Yi; Su, Ming-Sheng; Jiang, Shuai; Xue, Rou; Wu, Lu-Ling; Xie, Hui-Jing; Zhang, Yu-Zhuo; Liang, Zhi-Qun; Zeng, Nian-Kai (Phytotaxa, 2020)
The morphology and phylogenetic relationships of species of Hourangia (Boletaceae, Boletales) from China were investigated. Five phylogenetic species are recognized in the country; two of them, H. densisquamata and H. dilatata, are described as new; two of them, H. cheoi and H. nigropunctata, are previously described taxa, and the remaining one is not described due to the paucity of material. Besides specimens of Hourangia, collections of Aureoboletus were also made during field trips in China. The morphological and molecular data indicated that some collections labeled as A. cf. venustus or identified as A. venustus in previous studies represented a new species, therefore the new species A. erythraeus is described, and A. venustus is redescribed. A key to all known taxa of Hourangia is also provided.